The 9p21.3 risk locus for coronary artery disease: A 10-year search for its mechanism. Issue 3 (June 2017) - Almontashiri, Naif A.M.
الملخص: يعتبرالموضع الخطر للقطعة رقم پ21.3 على كروموسوم رقم ٩ أول موضع يوصف لارتباطه بزيادة خطر الإصابة بالحوادث ذات الصلة بأمراض الشرايين التاجية، وعدد من الظواهر الأخرى. تحتوي هذه القطعة على ٥٩ من النوكليوتيدات المنفردة المتعددة الأشكال في منطقة، مع العديد من المحفزات بعيدة المدى، ومناطق طويلة من الحمض النووي الريبي بلا رموز، التي تؤثر على التعبير عن الجينات القريبة، والسيكلين المعتمد على الكيناز 2أ و2ب والمطلوبة للتحكم في تنظيم الانقسام المتسارع، وشيخوخة الخلايا العضلية الملساء الموجودة في الأوعية الدموية. أجريت عدة دراسات لتحديد الآلية الصحيحة بدقة لكيفية ممارسة هذا الموضع تأثيره المرضي لزيادة خطر الإصابة بالحوادث ذات الصلة بأمراض الشرايين التاجية. في هذه المراجعة، سوف نقوم بتسليط الضوء على أبرز ما تم إنجازه، ومعرفته فيما يتعلق بارتباط النمط الجيني-المظهري على الصعيدين الميكانيكي والمظهري. نظرا إلى الخطر العالي على السكان الذي يعزى للموضع الخطر للقطعة رقم پ21.3 على كروموسوم رقم ٩، وآلية المعرفة التي حصلنا عليها حتى الآن، بالإضافة إلى الجهود المستمرة، قد تساعد في تصميم جزيئات علاجية جديدة لتقليل خطر أمراض الشرايين التاجية والحوادث ذات الصلة. Abstract: The 9p21.3 risk locus is the first locus to be associated with an increased risk of coronary artery disease (CAD)-related events and many other phenotypes. This locus contains 59 single nucleotide polymorphisms (SNPs) in a region with multiple long range enhancers and long non-coding RNAs (lncRNAs) that affect the expression of neighbouring genes, cyclin-dependent kinase 2A and 2B (CDKN2A and CDKN2B), which are required for controlling vascular smooth muscle cell proliferation and ageing. Several studies have attempted to identify the precise mechanism by which this locus exerts its pathogenic effect to increase the risk of CAD-related events. In this review, we will highlight the major advances in our understanding of the genotype–phenotype correlation at the mechanistic and phenotypic levels. The high population attributable risk of the 9p21.3 risk locus, mechanistic knowledge acquired thus far, and ongoing research efforts could facilitate the design of novel therapeutic molecules to reduce the risk of CAD and its related events.